Research in Halal Health Tourism Development - Marlina, Lina (SMART Insight, 2025)
Halal health tourism goes beyond individual medical treatments and encompasses a holistic environment that aligns with Islamic values, including a hospital environment consistent with Islamic ethics. This comprehensive offering becomes an important competitive factor among health tourism destinations. This study aims to examine the development of research on the topic of